Participation of the Tatars in the Activities of the Country Muslim Bureau of Turkestan - Rasulova Rislig’oy Abdullajanovna (Zien Journals, 2022)
This article discusses the fact that the Tatars worked not only in the Muslim Bureau of the Turkestan region, but also in the Muslim Bureau of the Fergana region. Among the Muslim population of the country, the Tatars stand out for their activity in local socio-political, military, cultural and educational processes. Thus, it is noted that the Tatars consider it expedient to actively participate in the socio-political life of the country, to involve representatives of the rural population of the country in active actions in these processes
Keywords: Muslim Bureau; propaganda; printing house; publishing house